Utilitas Ragam Media Digital dan Stuktur Persaingan Pasar antar Desa Wisata di Kawasan Perbukitan Menoreh - Antonius Budisusila; Victoria Sundari Handoko (Indonesian Journal of Tourism and Leisure, 2023)
The results of previous research on tourism digitization tend to legitimize the success of optimizing tourism digitization. These studies use the "single case" of tourist villages and digital platforms. Digitalization is not fully effective in supporting tourism performance. The purpose of this research is to reveal the utility of various digital media and tourist destinations in the structure of market competition. This study uses descriptive qualitative research methods. The study found that village tourism types are categorized into mass, live-in and religious tourism. All villages vary digital media in dissimilar preferences. Market structure analysis ensures that a small number of tourist villages become market leaders-forming monopoly market structure, while the majority are peripheral tourism villages. Digital multimedia options and types of tours are placed to win the performance. Four digitization and performance patterns are stated as effective, ineffective, not yet effective, and not digitalized. In mass tourism, multimedia is too effective in supporting the position of market leader.  In live-in and religious tourism villages, it was found to be ineffective and not digitized, but the characteristics of these two types of villages need another performance review approach. This study suggests important policies are needed to improve market structure.